Technology Entrepreneurship in Real Estate Sector Development in India : PPP Model - Solomon, Priya; Aggarwal, Tanu (Indian Journal of Finance, 2020)
The role of technology entrepreneurship and public and private partnership (PPP) have been considered important for real estate sector development in India. This study intended to find the role of public and private banks to promote and support technology entrepreneurship in India and to study the impact of residential loans, commercial loans, real estate advances, and indirect loans by public sector (SBI, PNB, Canara Bank, IDBI Bank, and Indian Bank) and private sector (HDFC Bank, ICICI Bank, Axis Bank, Yes Bank) banks on the total real estate sector development in India for strengthening the impact of technology entrepreneurship in India by using partial least squares structural equation modelling (PL-SEM).The banks like State Bank of India (SBI) and HDFC Bank were found to play a major role to promote and support technology entrepreneurship in India with the help of PPP model like the introduction of property festival online with private players like Snapdeal.com, MagicBricks.com with SBI and HDFCRed.com by HDFC Bank in assisting the property buyers which led to an increase in the role of public and private partnership projects (PPP) in India. Further, the partial least squares structural equation modelling was employed, which showed that there was an impact of the residential loans, commercial loans, real estate advances, and indirect loans by banks on the total real estate sector development in India for strengthening the impact of technology entrepreneurship in India.